XPS Characterization of TiO2 Nanotubes Growth on the Surface of the Ti15Zr15Mo Alloy for Biomedical Applications - Konatu, Reginaldo Toshihiro [UNESP] (2023)
Ti15Zr15Mo (TMZ alloy) has been studied in recent years for biomedical applications, mainly due to phase beta formation. From the surface modification, it is possible to associate the volume and surface properties with a better biomedical response. This study aimed to evaluate the possibility of using anodization to obtain TiO2 nanotubes due to the presence of valve-type metal (Zr) in their composition. X-ray photoelectron spectroscopy (XPS) was performed to determine the surface chemical composition in both after-processing conditions (passive layer) and after-processing plus anodization (TiO2 nanotube growth). The anodization resulted in nanotubes with diameters and thicknesses of 126 ± 35 and 1294 ± 193 nm, respectively, and predominated anatase phase. Compared to the passive layer of titanium, which is less than ~10 nm, the oxide layer formed was continuous and thicker. High-resolution spectra revealed that the oxide layer of the element alloys contained different oxidation states. The major phase in all depths for the nanotube samples was TiO2. While the stable form of each oxide was found to predominate on the surface, the inner part of the oxide layer consisted of suboxides and metallic forms. This composition included different oxidation states of the substrate elements Ti, Zr, and Mo.